2020
DOI: 10.3389/fneur.2020.01032
|View full text |Cite
|
Sign up to set email alerts
|

Preferentially Disrupted Core Hubs Within the Default-Mode Network in Patients With End-Stage Renal Disease: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Neuroimaging evidence implies that cognitive impairment in patients with end-stage renal disease (ESRD) is related to the disruption of the default-mode network (DMN). The DMN can be divided into three functionally independent subsystems, which include the cortical hub subsystem [consisting of the posterior cingulate cortex (PCC) and the anterior medial prefrontal cortex (aMPFC)], the dorsal medial prefrontal cortex (dMPFC) subsystem, and the medial temporal lobe (MTL) subsystem. However, it is unknown how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Because of the renal failure, the serum creatinine and urea levels were significantly increased in patients with ESRD. Previous researchers have found that the serum creatinine and urea levels were correlated with altered spontaneous brain activity and functional integration ( 15 , 25 , 39 , 40 ). However, in our study, serum creatinine and urea levels showed no correlation with ALFF values or Z scores of abnormal FC in the brain regions.…”
Section: Discussionmentioning
confidence: 98%
“…Because of the renal failure, the serum creatinine and urea levels were significantly increased in patients with ESRD. Previous researchers have found that the serum creatinine and urea levels were correlated with altered spontaneous brain activity and functional integration ( 15 , 25 , 39 , 40 ). However, in our study, serum creatinine and urea levels showed no correlation with ALFF values or Z scores of abnormal FC in the brain regions.…”
Section: Discussionmentioning
confidence: 98%
“…A number of previous rs-fMRI studies have also con rmed that ESRD patients showed altered ReHo, ALFF values and FC in the DMN region, which was consistent with the results of this study. The results indicated that decreased synchronization of activity in the DMN region may be the neuropathological mechanism of overall cognitive impairment in patients with ESRD [30][31][32][33].…”
Section: Discussionmentioning
confidence: 92%
“…These functional impairments of the DMN regions may influence the normal interactions between DMN subnetworks. Indeed, a recent study did demonstrate that patients with ESRD exhibit significantly lower FC between the two DMN hubs (i.e., the posterior cingulate cortex (PCC) and the anterior medial prefrontal cortex) and between the two DMN subnetworks (i.e., the dorsal medial prefrontal cortex subnetwork and the medial temporal lobe subnetwork) compared to HCs ( Ma et al, 2020 ). Evidences from these studies suggest functional deficits of the DMN regions and abnormal functional interactions of the DMN subnetworks, and thus support our findings.…”
Section: Discussionmentioning
confidence: 99%